2019
DOI: 10.1002/jmr.2814
|View full text |Cite
|
Sign up to set email alerts
|

Eriodictyol and naringenin inhibit the formation of AGEs: An in vitro and molecular interaction study

Abstract: Maillard reaction occurs between the carbonyl group of reducing sugars and the free amino groups of protein, which eventually results in the formation and accumulation of advanced glycation end products (AGEs) irreversibly. Excessive production of AGEs is associated with many diseases, such as Alzheimer disease, neuropathy, retinopathy, and nephropathy. In this study, the effects of eriodictyol and naringenin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Almost every change of lysine in glycated BSA with fructose was attributed to formation of carboxymethylysine (CML) [9]. On the other hand, the effect on albumin exposed to MGO caused a greater increase in fluorescence intensity, which is in line with other results [67,68]. The irreversible changes generated by glycation of MGO in BSA are highly selective for arginine residues, with some modifications of lysine and amino-terminal groups [69,70].…”
Section: Plos Onesupporting
confidence: 64%
“…Almost every change of lysine in glycated BSA with fructose was attributed to formation of carboxymethylysine (CML) [9]. On the other hand, the effect on albumin exposed to MGO caused a greater increase in fluorescence intensity, which is in line with other results [67,68]. The irreversible changes generated by glycation of MGO in BSA are highly selective for arginine residues, with some modifications of lysine and amino-terminal groups [69,70].…”
Section: Plos Onesupporting
confidence: 64%
“…This result indicated that MGO not only directly damage cells, but also indirectly induce cell damage by the formation of AGEs [66] . Previous spectroscopy experiments in our laboratory showed that MGO and BSA can quickly generate AGEs [19,25] . Overexpression of AGEs receptors was also found in leukocytes exposed to MGO [67] .…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the results of previous studies in our laboratory have proved that the reaction between MGO and bovine serum albumin (BSA) could quickly generate AGEs [19,25] . Both the analysis of the transcriptome of HEK293 cells and the expression profile of HEK293 in the human protein atlas database showed that they had the ability to express kidney development [26,27] .…”
Section: Introductionmentioning
confidence: 96%
“…These interaction results indicate that several facilitated glycation sites of BSA were occupied, thereby blocking or suppressing the formation of AGEs. A previous investigation also reported that eriodictyol and naringenin interact with BSA by hydrogen bonds and hydrophobic interactions to inhibit AGE formation (Liu et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%